Regulation of fibrillins and modulators of TGFβ in fetal bovine and human ovaries. Issue 2 (August 2016) - Bastian, Nicole A; Bayne, Rosemary A; Hummitzsch, Katja; Hatzirodos, Nicholas; Bonner, Wendy M; Hartanti, Monica D; Irving-Rodgers, Helen F; Anderson, Richard A; Rodgers, Raymond J
Abstract : Fibrillins 1–3 are stromal extracellular matrix proteins that play important roles in regulating TGFβ activity, which stimulates fibroblasts to proliferate and synthesize collagen. In the developing ovary, the action of stroma is initially necessary for the formation of ovigerous cords and subsequently for the formation of follicles and the surface epithelium of the ovary. FBN3 is highly expressed only in early ovarian development and then it declines. In contrast, FBN1 and 2 are upregulated in later ovarian development. We examined the expression of FBN1–3 in bovine and human fetal ovaries. We used cell dispersion and monolayer culture, cell passaging and tissue culture. Cells were treated with growth factors, hormones or inhibitors to assess the regulation of expression of FBN1–3 . When bovine fetal ovarian tissue was cultured, FBN3 expression declined significantly. Treatment with TGFβ-1 increased FBN1 and FBN2 expression in bovine fibroblasts, but did not affect FBN3 expression. Additionally, in cultures of human fetal ovarian fibroblasts (9–17weeks gestational age), the expression of FBN1 and FBN2 increased with passage, whereas FBN3 dramatically decreased. Treatment with activin A and a TGFβ family signaling inhibitor, SB431542, differentially regulated the expression of a range of modulators of TGFβ signaling and of other growth factors in cultured human fetal ovarian fibroblasts suggesting that TGFβ signaling is differentially involved in the regulation of ovarian fibroblasts. Additionally, since the changes in FBN1–3 expression that occur in vitro are those that occur with increasing gestational age in vivo, we suggest that the fetal ovarian fibroblasts mature in vitro .